2010
DOI: 10.1111/j.1365-2036.2010.04469.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dose and timing of esomeprazole administration on 24‐h, daytime and night‐time acid inhibition in healthy volunteers

Abstract: SUMMARY BackgroundSymptoms of gastro-oesophageal reflux disease (GERD) may persist despite daily treatment with a proton pump inhibitor (PPI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
2
24
2
Order By: Relevance
“…Esomeprazole 20 mg twice-daily (split dose) resulted in 76.5 % intragastric pH > 4 over 24 h as compared with esomeprazole 40 mg daily ( AM ), which resulted in only 68.8 % intragastric pH > 4 over 24 h. Th e eff ect of the split dose was most notable during nighttime intragastric pH assessment as compared with a one-time dose (62.8 vs. 51.4 % respectively). Unlike the current study by Kinoshita et al ( 8 ), Wilder-Smith et al ( 12 ) demonstrated a dose-response eff ect of esomeprazole on intragastric pH. In their study, esomeprazole 40 mg twice-daily in a split dose provided the most effi cacious eff ect on % 24-h and nighttime intragastric pH > 4 (87.1 and 81 % , respectively).…”
Section: Th E Introduction Of the Proton Pump Inhibitor (Ppi) Class Ocontrasting
confidence: 88%
See 1 more Smart Citation
“…Esomeprazole 20 mg twice-daily (split dose) resulted in 76.5 % intragastric pH > 4 over 24 h as compared with esomeprazole 40 mg daily ( AM ), which resulted in only 68.8 % intragastric pH > 4 over 24 h. Th e eff ect of the split dose was most notable during nighttime intragastric pH assessment as compared with a one-time dose (62.8 vs. 51.4 % respectively). Unlike the current study by Kinoshita et al ( 8 ), Wilder-Smith et al ( 12 ) demonstrated a dose-response eff ect of esomeprazole on intragastric pH. In their study, esomeprazole 40 mg twice-daily in a split dose provided the most effi cacious eff ect on % 24-h and nighttime intragastric pH > 4 (87.1 and 81 % , respectively).…”
Section: Th E Introduction Of the Proton Pump Inhibitor (Ppi) Class Ocontrasting
confidence: 88%
“…In a study by Wilder-Smith et al ( 12 ), the authors evaluated the eff ect of diff erent esomeprazole regimens on 24-h intragastric pH. Esomeprazole 20 mg twice-daily (split dose) resulted in 76.5 % intragastric pH > 4 over 24 h as compared with esomeprazole 40 mg daily ( AM ), which resulted in only 68.8 % intragastric pH > 4 over 24 h. Th e eff ect of the split dose was most notable during nighttime intragastric pH assessment as compared with a one-time dose (62.8 vs. 51.4 % respectively).…”
Section: Th E Introduction Of the Proton Pump Inhibitor (Ppi) Class Omentioning
confidence: 98%
“…Using PPI before dinner rather than before breakfast might have more effectively controlled the reflux‐related awakenings during sleep. It has been shown that a PPI used before dinner provided better control of nGER than did the same PPI when used before breakfast . Nighttime symptoms, daytime sleepiness, and poorer sleep quality were significantly related to refractory GERD symptoms.…”
Section: Role Of Nocturnal Reflux Symptoms In Sleep Disordersmentioning
confidence: 99%
“…The impact on esophageal acid exposure during sleep may have been greater if esomeprazole had been given before dinner. It has been shown that a PPI given in the evening before dinner provides better control of nighttime reflux, as compared to the same PPI given in the morning before breakfast …”
Section: Discussionmentioning
confidence: 99%